Micronutrients and Leptospirosis: A Review of the Current Evidence - Herman, Heather S. (PLoS Negl Trop Dis, 2016)
BACKGROUND: Leptospirosis is one of the most widespread zoonoses and represents a major threat to human health. Due to the high burden of disease, limitations in diagnostics, and limited coverage and availability of effective human and veterinary vaccines, leptospirosis remains an important neglected zoonotic disease. Improved surveillance and identification of modifiable risk factors for leptospirosis are urgently needed to inform preventive interventions and reduce the risk and severity of Leptospira infection. METHODOLOGY/PRINCIPAL FINDINGS: This review was conducted to examine the evidence that links micronutrient status and Leptospira infection. A total of 56 studies were included in this review: 28 in vitro, 17 animal, and 11 observational human studies. Findings indicated that Leptospira infection is associated with higher iron and calcium concentrations and hypomagnesemia. CONCLUSIONS/SIGNIFICANCE: Few prospective studies and no randomized trials have been conducted to date to examine the potential role of micronutrients in Leptospira infection. The limited literature in this area constrains our ability to make specific recommendations; however, the roles of iron, calcium, and magnesium in leptospirosis represent important areas for future research. The role of micronutrients in leptospirosis risk and severity needs to be elucidated in larger prospective human studies to inform public health interventions.